Kierkegaard's journals and notebooks. - Kierkegaard, Søren, 1813-1855 (Princeton University Press, 2011)
For over a century, the Danish thinker Søren Kierkegaard (1813-55) has been at the center of a number of important discussions, concerning not only philosophy and theology, but also, more recently, fields such as social thought, psychology, and contemporary aesthetics, especially literary theory.Despite his relatively short life, Kierkegaard was an extraordinarily prolific writer, as attested to by the 26-volume Princeton University Press edition of all of his published writings. But Kierkegaard left behind nearly as muchunpublishedwriting, most of which consists of what are called his "journals and notebooks." Kierkegaard has long been recognized as one of history's great journal keepers, but only rather small portions of his journals and notebooks are what we usually understand by the term "diaries." By far the greater part of Kierkegaard's journals and notebooks consists of reflections on a myriad of subjects--philosophical, religious, political, personal. Studying his journals and notebooks takes us into his workshop, where we can see his entire universe of thought. We can witness the genesis of his published works, to be sure--but we can also see whole galaxies of concepts, new insights, and fragments, large and small, of partially (or almost entirely) completed but unpublished works.Kierkegaard's Journals and Notebooksenables us to see the thinker in dialogue with his times and with himself.Volume 5 of this 11-volume series includes five of Kierkegaard's important "NB" journals (Journals NB6 through NB10), covering the months from summer 1848 through early May 1849. This was a turbulent period both in the history of Denmark--which was experiencing the immediate aftermath of revolution and the fall of absolutism, a continuing war with the German states, and the replacement of the State Church with the Danish People's Church--and for Kierkegaard personally. The journals in the present volume include Kierkegaard's reactions to the political upheaval, a retrospective account of his audiences with King Christian VIII, deliberations about publishing an autobiographical explanation of his writings, and an increasingly harsh critique of the Danish Church. These journals also reflect Kierkegaard's deep concern over his collision with the satirical journalCorsair, an experience that helped radicalize his view of "essential Christianity" and caused him to ponder the meaning of martyrdom.Kierkegaard wrote his journals in a two-column format, one for his initial entries and the second for the extensive marginal comments that he added later. This edition of the journals reproduces this format, includes several photographs of original manuscript pages, and contains extensive scholarly commentary on the various entries and on the history of the manuscripts being reproduced.